The biopsychosocial and spiritual perspective on the readiness to quit smoking: a comprehensive review - Mohd Haazik Mohamed; Voo, Peter Su Kiong; Ismail Maakip; Fredie Robinson (Secholian Publication, 2022)
Smoking cessationis a major public health goal today as smoking has threatened the safety, health, and lives of millions of people in the global community. Therefore, the purpose of this study is to identify the role of biopsychosocial and spiritual factors towards the readiness to quit smoking and smoking cessation. The results of the study found that smoking behaviour adversely affects not only the biological aspects but also the psychological, social, and spiritual aspects. Apart from that, this study also found that the biological, psychological, social, and spiritual aspects also play an important role in determining the motivation of smokers to quit smoking holistically. Therefore, research and empirical evidence on the biopsychosocial and spiritual aspects are needed to help healthcare teams to identify the barriers and motivating factors to quit smoking.